Decision Making Of Hand Tractor Gear Box Designs - Ahmad Fatih Fudhla (Department Industrial Engineering, University of Muhammadiyah Malang, 2013)
Decision making on selection of hand tractor Gear Transmission Box (GTB) “Improvement Designs” is carried out according to many criteria. Based on the focus group and brainstorm performed by product-development teams, seven criteria are finally identified as follows; Material corrosion resistance, Manufacturability, The ability of the design to withstand the maximum load operation, influence on the other components process, manufacturing cost, mass of GTB design, and processing time. Those criteria are categorized into positive and negative characteristics. Positive criteria indicate that score which is the greater the better, by contrast, negative is the less the better. There are 3 alternatives namely Initial Design, Design 1 and Design 2. The selection is performed based on Analytic Hierarchy Process (AHP) Method. The evaluation is analyzed separately according to each category. The best alternative is the one which has the highest ratio between positive and negative criteria.